Volume 5: Manufacturing Materials and Metallurgy; Ceramics; Structures and Dynamics; Controls, Diagnostics and Instrumentation; 1995
DOI: 10.1115/95-gt-235
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Fatigue Testing of Candidate Ceramic Materials for Turbine Engines to Determine Slow-Crack-Growth Parameters

Abstract: The purpose of this study was to evaluate the mechanical strength and slow-crack-growth parameter values for two commercially available silicon nitrides, SN-88 and NT164, at three high temperature conditions. Weibull analysis and dynamic fatigue slow-crack-growth parameters were used to characterize the material strength and resistance to slow crack growth at high temperatures for use in life prediction models. Although both materials are commercially available Si3N4, their high temperature behavior was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…As a consequence, the a consequence of the ytterbium-silicon-oxynitride grain boundary phase undergoing some softening. This phenomenon has been reported for this material in flexure loading at 1350°C (Osborne and Graves, 1995).…”
Section: Youne's Modulus Of Si3n4 and Sicsupporting
confidence: 83%
See 1 more Smart Citation
“…As a consequence, the a consequence of the ytterbium-silicon-oxynitride grain boundary phase undergoing some softening. This phenomenon has been reported for this material in flexure loading at 1350°C (Osborne and Graves, 1995).…”
Section: Youne's Modulus Of Si3n4 and Sicsupporting
confidence: 83%
“…Silicon nitride (Si3s14) and silicon carbide (SiC) ceramics are leading candidates for use as structural components, e.g., nozzles and combustor tiles (Parthasarathy et at, 1995), in advanced industrial gas turbine engines. The utilization of Si3Is14 or SiC over more traditional alloys offers several advantages such as higher temperature capability (and an associated increased operating efficiency), reduced weight and inertia effects, and the potential design and use of non-cooled components.…”
Section: Introductionmentioning
confidence: 99%
“…Previous references to the creep and rupture of the silicon nitride of this study can be found in the literature. [15][16][17][18][19][20][21][22][23] The data from this study are part of a much larger engineering study of the suitability of monolithic silicon nitride for gas turbine engine applications. 24…”
Section: Introductionmentioning
confidence: 99%